The Books of Ezra and Nehemiah - Harrington, Hannah K. (Grand Rapids: William B. Eerdmans publishing company, 2022)
"A Christian commentary on the books of Ezra and Nehemiah rooted in an understanding of these biblical texts as some of the earliest Jewish literature of the Second Temple era"--
"The books of Ezra and Nehemiah represent a significant turning point in biblical history. They tell the story not only of the temple in Jerusalem being rebuilt but also of God resurrecting his people from the death of exile. Hannah Harrington thus begins her commentary with an evocative description of these books as "the story of a new Israel forged out of the old" and "the text of a people clinging to their genealogical past and attempting to preserve their heritage while walking forward into uncharted territory." Throughout this commentary, Harrington combines analytical research on the language and culture behind the books of Ezra and Nehemiah with challenging thoughts for the Christian church today, bringing to bear a unique perspective on these books not as the end of Old Testament history but as some of the earliest Jewish books written during the Second Temple period. Accordingly, Harrington incorporates a wealth of information from other Jewish literature from this time period to freshly illuminate many of the topics and issues at hand while focusing on the interpretation and use of these books for Christian life today"--
Includes bibliographical references (pages xxi-xxxiv) and indexes.
Keywords: Bible. -- Commentaries; Bible. -- Commentaries; RELIGION / Biblical Commentary / Old Testament / Historical Books; RELIGION / Biblical Studies / Old Testament / Historical Books